A Highly Luminescent Tetramer from a Weakly Emitting Monomer: Acid‐ and Redox‐Controlled Multiple Complexation by Cucurbit[7]uril. Issue 23 (13th May 2014) - Bergamini, Giacomo; Fermi, Andrea; Marchini, Marianna; Locritani, Mirko; Credi, Alberto; Venturi, Margherita; Negri, Fabrizia; Ceroni, Paola; Baroncini, Massimo
Abstract The tetrahedral, shape‐persistent molecule 14+, containing four pyridylpyridinium units connected through a central carbon atom, exhibits unexpected photophysical properties including a substantially redshifted absorption (2350 cm−1) and a very strong fluorescence (Φem=40 %), compared with the monomer 2+ (Φem=0.4 %). Density functional theory calculations on the structure and spectroscopic properties of 14+ and 2+ show that exciton interactions, homoconjugation, and orbital nature account for the observed differences in their photophysical properties. The protonated tetramer binds four cucurbit[7]uril molecules and the host/guest interactions can be controlled by chemical (acid/base) as well as redox stimuli.